Carbon Stock Estimation of Mangrove Forest in Village Margasari Sub-District Labuhan Maringgai District East Lampung - Cahyaning Windarni; Agus Setiawan; Rusita Rusita (Department of Forestry, Faculty of Agriculture, University of Lampung, 2018)
Increasing CO2 in the atmosphere and decreasing amount of forest as absorb CO2are factors which was the underlying repercussion of climate change. One of solutions for decreasing CO2 concentration through the forest vegetation’s development and emendation. Mangrove forest estimated that effectively absorb carbon through photosynthesis. The purpose of the studyis to estimate the stand and litter carbon stock of mangrove forest. The research used line transectmethod. The first line and plot determined randomly then the next lineand plots was sistematically. The observation plots had measurement with amount of 20m x 20m with spacing between plot in line 20 m with total 20 plots. Each plot was measured diameter just ≥ 5 cm. Each plot made observations litter sub plots with amount of 0,5 m x 0,5 m. Carbon estimation of stand biomass using allometric equations B = 0,1848D2.3624 and litter biomass using total dry weight. Carbon concentration of organic material typically contains around 46% thus multiplying the biomass by 46%. The average biomass of mangrove forests amounted to 431,78 tons/ha. Carbon estimated of mangrove stand was 197,36 ton/ha and litter carbon was 1,25 ton/ha, based on the research total of carbon mangrove forest was198,61 ton/ha. Keywords:carbon above ground,line transect, mangrove forest